What do they really “Meme”? A multimodal study on ‘Siakap Langkawi’ memes as tools for humour and marketing - How, Cherish (Penerbit Universiti Kebangsaan Malaysia, 2022)
The popularity of memes has increased in this modern era as they can be highly accessible on the internet. They are significant as communication tools on social media such as tools for humour and marketing. Studies commonly explored memes in the field of marketing and business, politics, and even their effects on social media users. However, studies which focus on memes from a multimodal discourse perspective, particularly in the Malaysian context in relation to the Siakap Langkawi issue, seem to be fairly scarce. Hence, through the lens of the three-dimensional model by Fairclough and the three dimensions of memes by Shifman, a multimodal study on memes with the issue on Siakap Langkawi as the theme is conducted. Specifically, this study examines the meanings and messages of the memes. Findings show that the memes in this study constitute a form of mockery, protest, and resistance towards the Siakap Langkawi issue as Malaysians stand for the rights of consumers. Additionally, pantun and famous memes were used and recreated; the salience of word font and images contribute greatly to the intended meaning and messages of these memes. This study is timely as it provides a detailed analysis of the structures of memes and categorises them into themes to show common trends. Such a move ultimately contributes to our understanding of the ways Malaysian social media users express their thoughts, messages, and dissent on the Siakap Langkawi issue via memes.